Optical fiber-based plasmonic biosensors : trends, techniques, and applications /: trends, techniques, and applications. (2022) - (Physics professor), Kumar, Santosh; Saha, Chinmoy; Jha, Rajan; Agrawal, Niteshkumar
No abstract available